Site planning for cluster housing - Untermann, Richard K.; Small, Robert E. (New York : Van Nostrand Reinhold Company, Inc., 1977)
This book is about the process of physically designing cluster housing environments. It was written with a sense of urgency; there is great need for all the participants in the housing industry to develop new and improved skills in the planning and design of this reemerging house/settlement form.
Part One. Small sites -- Part Two. Large sites -- Index.
Includes bibliographical references and index.
Keywords: CLUSTER HOUSING -- UNITED STATES